Performance of microfinance institutions in Burkina Faso - Youssoufou Congo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This study tests the performance of microfinance institutions (MFIs) in Burkina Faso using indicators such as the sustainable interest rate and the subsidy dependence index. The results indicate that MFIs outreach performance remains very low compared with potential demand, and the factors responsible appear to be both the refusal of most MFIs to mobilize local savings and the high costs of supply of microfinancial services. The results also show that MFIs are not viable and sustainable. Their interest rates are kept low and do not allow them to cover all the costs. In addition, the results indicate that MFIs are dependent on subsidies. However, the oldest MFIs and/or institutions providing deposit services have the lowest subsidy dependence index. It is suggested that more attention should be placed on savings mobilization and ceilings on interest rates should be removed in order to allow MFIs to charge sustainable interest rates. – microfinance ; performance indicators ; Burkina Faso
Keywords: E21; E43; G10; G20; 330; Unternehmensentwicklung; Burkina Faso; Mikrofinanz